Dynamics of actors in innovation ecosystems' analytical structures - Camila Coletto; Leonardo Caliari; Dércio Bernardes-de-Souza; Daniela Callegaro de Menezes (Innovation & Management Review, 2024)
Purpose - The link between theory and practice in innovation studies still has some gaps, despite scholars' efforts to illustrate and identify them in real-world situations. To fully understand the dynamics of the innovation ecosystem, it is crucial to consider key actors and their roles and recognize their impact on ecosystem outcomes. Therefore, this paper seeks to discuss how analytical structures of innovation ecosystems address the dynamics of actors and their contribution to the ecosystem outcomes. Design/methodology/approach - A research protocol was developed to query the Web of Science database to identify analytical structures of innovation ecosystems based on pre-established criteria. Findings - The dynamics of actors interfere with their contribution to value creation. That is, the actor changes his contribution. Therefore, depending on the ecosystem's value proposition, the activities and dynamics of the actors change over time. Originality/value - It contributes to advancing the discussion of innovation ecosystems, addressing insights into the dynamics of actors in different analytical structures. The essay proposal considers innovation ecosystems' evolutionary aspects, value propositions and exchange. In addition, the importance of orchestration in the various stages of the ecosystem is highlighted.
Keywords: 650; Innovation ecosystem; Analytical structures; Actors dynamics; Proposition